Towards Biodiverse Urban Public Spaces: A Morphological Study in Milan - Fabio Lepratto; Francesca Zanotto (Journal of Contemporary Urban Affairs, 2024)
This study explores the role of architectural composition and urban design in enhancing urban biodiversity, which is crucial for improving ecosystem services and overall urban sustainability. It addresses a gap in the literature by providing empirical evidence on how specific morphological characteristics in urban regeneration projects can support biodiversity, emphasizing the overlooked potential of architectural morphologies in urban greening strategies. Focusing on five recent urban regeneration projects in Milan, the study conducts a detailed analysis of built volumes and green areas. Quantitative measurements, such as green area compactness, perimeter edge continuity, and building front permeability, were combined with qualitative assessments to identify correlations between urban morphology and biodiversity potential. The analysis revealed three distinct urban morphologies—"Central Park," "Fluid Park," and "Garden Between Houses"—each offering unique conditions for accessibility and biodiversity development. These morphologies demonstrate varying capacities for conserving, promoting, and implementing urban biodiversity, depending on their interaction with the surrounding urban fabric. By establishing a clear correlation between urban morphology and biodiversity potential, this research highlights the critical role that architects and urban designers play in addressing the emerging challenge of enhancing urban biodiversity. It provides valuable insights for future urban regeneration projects aimed at fostering sustainable and biodiverse urban environments.